Etiqueta y protocolo y su incidencia en la organización de eventos a cargo de las secretarias (os) de la Unidad Educativa Eugenio Espejo del Cantón Babahoyo Provincia de los Ríos. - Valverde Poveda, Adán Isaías (2016)
This research work intends to execute the reality of Etiquette and Protocol and its impact on the organization of events by the Secretaries (os) of the Education Unit Eugenio Espejo Canton Babahoyo the Rios Province. We often hear of protocol and etiquette, but many times or consider synonyms or entirely unknown scope and meaning. These concepts tend to be confused because of the elements they have in common. "Protocol" is the set of rules established for official ceremonies and formalities social, diplomatic, military, and institutional, these rules are necessary to establish a relationship of friendship and respect between the parties. While "tag" could be identified as the manner or way we behave or we turned up at these social events. The etiquette and protocol involve behavioral standards established to make social life more pleasant, but the difference is marked on the label regulates personal behavior and protocol establishes the criteria for treatment and origin of a person or institution. I found during my short life to privileged educated beings, which have acquired their exquisiteness in an atmosphere of peace, honesty and good manners inculcated from childhood, as to the protocol rules, it is good to emphasize that they can vary according to the customs and behaviors.